Neonatal outcome of second baby versus first baby in twins delivered vaginally: a comparative study - Srivastava, Shubhi; Borgohain, D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The incidence of twinning has been increasing due to assisted reproductive technology. Despite substantial concerns over the well-being of the second twin with regard to intra partum events, outcome studies on this issue are conflicting. Some have reported no increase in perinatal complications, while others showed significant associations between labor and delivery of the second twin and increased perinatal morbidity and mortality. Methods: All pregnant women of twin pregnancy at more than 28 weeks of gestation, first twin with cephalic presentation were selected for study. Intrauterine death of either of the twins, pregnancies complicated or fetal malformations and those with contraindication to vaginal birth were excluded. After delivery, APGAR score, birth weight, complications, time interval between deliveries, NICU admission and condition on discharge of each baby was noted. Results: Out of 106 women with twin pregnancy 89 of them delivered vaginally, there was statistically no significant difference of live births, still births, early neonatal mortality in the first and second born twins. Neonatal morbidity was more in the second twin than the first twin (23.33% versus 21.11%).Out of all NICU admissions 47.5% were for the first twin and 52.5% for the second twin. Conclusions: Twin vaginal delivery is safe in first cephalic presentation in twin pregnancy. Caution should be taken while delivering babies <1500gm, gestational age <34 weeks, as vaginal delivery in these conditions is associated with increased early neonatal morbidity and neonatal mortality.